Effect of aggregation of a cationic phthalocyanine in micelles and in the presence of human serum albumin - Rodriguez, Myriam E. (2006)
The photophysical properties of tetrakis(1,1-dimethyl-2-trimethylammonium) ethylphthalocyaninato zinc(II) tetraiodide (I) - a water-soluble cationic phthalocyanine - are presented in the presence of human serum albumin (HSA) and in micelles of sodium dodecylsulfate (SDS) and hexadecyltrimethylammonium chloride (CTAC). Spectrophotometric measurements showed that the surfactants SDS and CTAC induce monomerization of I, although the latter less efficiently than the former. This effect is less pronounced in the presence of HSA. The strength of this effect is evaluated through dimerization constants, which are K d = (5 ± 1) × 105 M-1 in SDS, (1.5 ± 0.5) × 106 M-1 in CTAC, and (1.8 ± 0.9) × 106 M-1 in HSA. Fluorescence experiments confirm that aggregation of I drops as the concentration of surfactant is raised. Triplet quantum yields also decreased upon aggregation and were ΦT = 0.59, 0.16, and < 0.01 in SDS, CTAC, and HSA, respectively. These results indicate that the affinity of I for the environment is not just due to ionic interactions; hydrophobic interactions play an equally important role.